4D Scanning - Dynamic View on Body Measurements - Anke Klepser; Simone Morlock (Communications in Development and Assembling of Textile Products, 2020)
Fitting test in movement are an important issue not only in work and sports wear since garment should not restrict the range of motion. Therefore, dynamic anthropometry is a major research topic. Until now, only static position could be captured. Still, it is not known how body geometry changes in dynamic movement. In IGF project “Mobilityrestrictions” photogrammetry scanner “Little Alice” was investigated regarding 4D. It enables serial recording in seconds. The aim of the research project was beside other to identify differences between static and dynamic body measurements.